Effects of antipsychotic drugs on cardiovascular variability in participants with bipolar disorder. (3rd January 2014) - Linder, Jonathan R.; Sodhi, Simrit K.; Haynes, William G.; Fiedorowicz, Jess G.
<x xml:space="preserve">Abstract</x> Objective The risk for cardiovascular diseases is elevated in persons with bipolar disorder. However, it remains unknown how much of this excess risk is secondary to pharmacologic treatment. We tested the hypothesis that current and cumulative antipsychotic drug exposure is associated with increased cardiovascular risk as indicated by lower heart rate variability (HRV) and increased blood pressure variability (BPV). Methods Fifty‐five individuals with bipolar disorder (33 ± 7 years; 67% female) underwent noninvasive electrocardiogram assessment of time‐domain and frequency‐domain HRV, as well as BPV analysis. Medication histories were obtained through systematic review of pharmacy records for the past 5 years. Results Current antipsychotic exposure was associated with lower standard deviation of NN intervals. Second‐generation antipsychotics were associated with lower standard deviation of NN intervals and root mean square of successive differences. There was no significant relationship between 5‐year antipsychotic exposure and HRV in subjects with bipolar disorder. Exploratory analysis revealed a possible link between selective serotonin reuptake inhibitor exposure and increased low‐frequency spectral HRV. Conclusions Current antipsychotic use (particularly second‐generation antipsychotics with high affinities for the D2S receptor) is associated with reduced autonomic‐mediated variability of the HR. The absence of an association with cumulative exposure suggests that the effects are acute in onset and may therefore relate more to altered autonomic function than structural cardiovascular abnormalities. Future studies should prospectively examine effects of these antipsychotics on autonomic function. Copyright © 2014 John Wiley & Sons, Ltd.